Правове регулювання та тенденції розвитку дактилоскопічного обліку в Україні - Книженко, С. О.; Knyzhenko , S. O.; Шарабан, О.; Sharaban, O.; Книженко Світлана (Соціологія права. - 2023. - Вип. 1-2. - С. 46-50, 2023)
Розглянуто актуальні питання використання та правового регулювання дактилоскопічних обліків в Україні. На Міністерство внутрішніх справ України, Національну поліцію України покладені обов’язки щодо здійснення забезпечення національної безпеки. Згідно чинного законодавства поліція наповнює та підтримує в актуальному стані реєстри та бази даних, що входять до єдиної інформаційної системи Міністерства внутрішніх справ України. Одним із видів криміналістичних обліків є дактилоскопічний, який належить до біометричних даних особи й підпадає під захист держави як персональні дані. На жаль, є непоодинокі випадки несвоєчасного знаття з обліку об’єктів реєстрації, що порушує права громадян. Правове регулювання збирання біометричних даних у вигляді відбитків пальців рук людини є вкрай важливими та актуальними оскільки багато питань залишається не врегульованими на законодавчому рівні. Відзначено, що сьогодні в Україні виникла необхідність у розробці нормативно-правової бази, загальних положень, принципів і вимог до організації системи біометричної реєстрації з враху- ванням досвіду передових країн світу. Запропоновано прийняти закон про біометричну реєстрацію, який би включав в себе різні види біометричних технологій (а не тільки відбитки пальців рук чи ДНК) з можливістю їх комбінування.

Ministry of Internal Affairs of Ukraine and the National Police of Ukraine are entrusted with the responsibility of ensuring national security. According to the current legislation, the police fills and maintains up-to-date the registers and databases included in the unified information system of the Ministry of Internal Affairs of Ukraine. One of the types of forensic records is dactyloscopic, which belongs to the biometric data of a person and is subject to state protection as personal data. Unfortunately, there are rare cases of untimely knowledge of the accounting of registration objects, which violates the rights of citizens. Legal regulation of the collection of biometric data in the form of human fingerprints is extremely important and relevant, as many issues remain unsettled at the legislative level. The article names dactyloscopic systems operating today on the territory of Ukraine and reveals their importance in the investigation of criminal offenses. Defined laws and by-laws regulating the legal procedure for keeping such forensic records. Contradictions of bylaws among themselves are revealed and their obsolescence is indicated. The experience of foreign countries regarding the types of biometric registration and the procedure for its legal regulation is analyzed. The authors suggest using the practice of foreign countries to introduce multimodal biometric technologies. In the end, it was noted that today in Ukraine there is a need to develop a regulatory framework, general provisions, principles and requirements for the organization of the biometric registration system, taking into account the experience of the leading countries of the world. It is advisable to adopt a law on biometric registration, which would include various types of biometric technologies (not only fingerprints or DNA) with the possibility of combining them.

Раскрыты проблемы и перспективы усовершенствования правового регулирования дактилоскопического учета в Украине. Отмечено, что сегодня в Украине возникла необходимость в разработке нормативно-правовой базы, общие положения, принципы и требования к организации системы биометрической регистрации с учетом опыта передовых стран мира. Предложено принять закон о биометрической регистрации, который бы включал в себя разные виды биометрических технологий (а не только отпечатки пальцев рук или ДНК) с возможностью их комбинирования.
Legal regulation and development trends of dactyloscopic accounting in Ukraine
Keywords: правове регулювання; legal regulation; правовое регулирование; дактилоскопічний облік; dactyloscopic accounting; дактилоскопический учет; відбитки пальців рук; fingerprints; отпечатки пальцев рук; біометрична реєстрація; biometric registration; биометрическая регистрация